Restructuring the Chinese city : changing society, economy and space - Ma, Laurence J. C., 1937-; Wu, Fulong (Routledge, 2005)
Restructuring the Chinese City is an indispensable text for Chinese specialists, urban scholars and advanced students in urban geography, urban planning and China studies.